Proto-algorithmic war: how the Iraq War became a laboratory for algorithmic logics - Hristova, Stefka (Social and Cultural Studies of Robots and AI, 2022)
Chapter 1: Algorithmic Logics and War -- Chapter 2: Data Lands/Data Subjects -- Chapter 3: Taxonomies Of Enmity -- Chapter 4: Data Replay -- Chapter 5: Veridiction Training -- Chapter 6: Automation, Trust, Responsibility -- Chapter 7: Conclusion: Beyond War.